Vikings. Season 3 [videorecording (Blu-Ray)] - Robson, Ben; Durand, Kevin; Bluteau, Lothaire; Polanski, Morgane; Blagden, George, 1989-; Fimmel, Travis, 1979-; Winnick, Katheryn; Standen, Clive (20th Century Fox Home Entertainment, 2015)
With Ragnar now king, he faces more foes than ever in Season Three but out of all the rivals, there's one Viking in particular he should watch out for: Erlendur. The only surviving child of King Horik, his entire family slaughtered during a brawl between the King of Denmark and the legendary Norse ruler, during the Season two finale. Ragnar, impressed by Erlendur's idea of going to farm in England spares Erlendur's life.